ANALISIS POLA PENGEMBANGAN ZAKAT, INFAK DAN SEDEKAH SEBAGAI INSTRUMEN KEUANGAN PUBLIK ISLAM DI PROVINSI GORONTALO SERAMBI MADINAH - Kartin Baide; Zainuddin (Prodi Ekonomi Syariah Pascasarjana IAIN Sultan Amai Gorontalo, 2022)
Zakat has a central position in fiscal policy and public finances in the early days of Islam. Besides being the main source of income for Islamic countries at that time, zakat was also able to support state expenditures in the form of government expenditure and government transfers. Zakat is also able to influence the economic policies of the Islamic government to improve the welfare of the people, especially the weak. This study aims to describe how the pattern of development of zakat, infaq and alms as Islamic public financial instruments in the Province of Gorontalo Serambi Medina. The methodology of this research is to use qualitative research with a descriptive approach. Data collection techniques were carried out by interviews and documentation. The results of the analysis show that in the management of zakat, infaq and alms, the Gorontalo Provincial government provides APBD (Regional Revenue and Expenditure Budget) assistance as BAZNAS operational costs. This has been proven to increase the efficiency of collection and distribution of zakat at BAZNAS Gorontalo Province.